2016
DOI: 10.1073/pnas.1523629113
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of retinal projections to the central circadian pacemaker

Abstract: The suprachiasmatic nucleus (SCN) receives direct retinal input from the intrinsically photosensitive retinal ganglion cells (ipRGCs) for circadian photoentrainment. Interestingly, the SCN is the only brain region that receives equal inputs from the left and right eyes. Despite morphological assessments showing that axonal fibers originating from ipRGCs cover the entire SCN, physiological evidence suggests that only vasoactive intestinal polypeptide (VIP)/ gastrin-releasing peptide (GRP) cells located ventrall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(147 citation statements)
references
References 44 publications
9
138
0
Order By: Relevance
“…First, direct and indirect projections from light-capturing retinal ganglion cells reach neurons of the SCN, modulating their activity (Abrahamson and Moore, 2001;Edelstein and Amir, 1999;Fernandez et al, 2016;Michel et al, 2006;Nakamura et al, 2004). Depending on the phase of the receiving SCN neuron, light input can stimulate active firing of the neuron and modulate clock gene expression (Brown and Piggins, 2007;Hamada et al, 2001; but also see Drouyer et al, 2007, highlighting SCN heterogenetity in this response).…”
Section: The Regulation Of Daily Rhythms In Mammalsmentioning
confidence: 99%
“…First, direct and indirect projections from light-capturing retinal ganglion cells reach neurons of the SCN, modulating their activity (Abrahamson and Moore, 2001;Edelstein and Amir, 1999;Fernandez et al, 2016;Michel et al, 2006;Nakamura et al, 2004). Depending on the phase of the receiving SCN neuron, light input can stimulate active firing of the neuron and modulate clock gene expression (Brown and Piggins, 2007;Hamada et al, 2001; but also see Drouyer et al, 2007, highlighting SCN heterogenetity in this response).…”
Section: The Regulation Of Daily Rhythms In Mammalsmentioning
confidence: 99%
“…The retinothalamic system transmits critical information about circadian rhythms, thanks to which biological rhythms, the wake-sleep cycle are regulated, locomotive activity and food consumption change during a day, etc. Most fibers comprised in this system are axons of RGC [10,11]. There also is the centrifugal hypothalamoretinal pathway starting from the hypothalamic neurosecreting fibers and finishing in the RGC, etc.…”
Section: IIImentioning
confidence: 99%
“…There also is the centrifugal hypothalamoretinal pathway starting from the hypothalamic neurosecreting fibers and finishing in the RGC, etc. Nowadays it is well known that this pathway is used in regulating retinal vascular pressure, changing retinal electric potential, regulates light sensitivity and adaptation of the eyes to darkness [10,11]. This aspect is crucial in understanding some disorders in the visual system in PD, e.g., association of visual hallucinations with evening and/or night time, etc.…”
Section: IIImentioning
confidence: 99%
“…At least five different ipRGC subtypes (M 1 -M 5 ) (Ecker et al 2010;Schmidt et al 2011a) have been identified that project to non-image forming centres in the rodent brain, with the M 1 and M 2 subtypes likely to be homologous to the outer and inner stratifying melanopsin cells found in humans and non-human primates (Dacey et al 2005;Jusuf et al 2007;Liao et al 2016). A recent mouse study using single M 1 ipRGC axonal tracing and confocal microscopic analysis identified up to five different brain targets that received input from a single M 1 subtype ipRGC, indicating that a single ipRGC can affect brain areas involved in numerous lightmediated behaviours (Fernandez, Chang, Hattar & Chen 2016). Therefore, the correlation between poorer sleep efficiency and reduced PIPR may be attributed to individual M 1 ipRGCs projecting to both the SCN and OPN.…”
Section: 6mentioning
confidence: 99%
“…A more recent mouse study using single M 1 ipRGC axonal tracing and confocal microscopic analysis identified up to five different brain targets that received input from a single M 1 subtype ipRGC, indicating that a single retinal cell can affect brain areas involved in numerous light-mediated behaviours (Fernandez et al 2016).…”
Section: 3mentioning
confidence: 99%